2016
DOI: 10.1515/jpm-2016-0178
|View full text |Cite
|
Sign up to set email alerts
|

Maternal endothelial damage as a disorder shared by early preeclampsia, late preeclampsia and intrauterine growth restriction

Abstract: The higher values of disordered angiogenesis markers, endothelial damage markers and inflammatory markers both in the PE and the intrauterine growth restriction (IUGR) groups suggest the existence of shared disorders in the development of these pathologies. The correlations between disordered angiogenesis markers and endothelial damage markers argue in favor of a mutual relationship between these two processes in the development of pathologies evolving as secondary to placental ischemia. The results obtained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
2
8
0
1
Order By: Relevance
“…This low birth weight was also influenced by the prevalence of IGR in this group, which in our series was 23.8%, close to the 25% found in the study by Kongwattanakul et al [15]. SP is one of the main known causes of IGR and has an OR of 2.16 (95% CI, p = 0.026) according to Liu et al Both pathologies originate from anomalous placentation, which conditions increased resistance to uteroplacental flow and placental insufficiency secondary to the endothelial destruction of a low-resistance tissue subjected to high pressure (Kwiatkowski) [16].…”
Section: Discussionsupporting
confidence: 71%
“…This low birth weight was also influenced by the prevalence of IGR in this group, which in our series was 23.8%, close to the 25% found in the study by Kongwattanakul et al [15]. SP is one of the main known causes of IGR and has an OR of 2.16 (95% CI, p = 0.026) according to Liu et al Both pathologies originate from anomalous placentation, which conditions increased resistance to uteroplacental flow and placental insufficiency secondary to the endothelial destruction of a low-resistance tissue subjected to high pressure (Kwiatkowski) [16].…”
Section: Discussionsupporting
confidence: 71%
“…Several biomarkers of PE, including vascular endothelial growth factor (VEGF), placental growth factor (PlGF), and soluble Flt-1, are involved in angiogenesis. In pregnant women with PE and/or IUGR, higher concentrations of soluble Flt-1 and lower concentrations of PlGF were found compared to the controls [23]. Low levels of angiogenic proteins on the first postnatal day in infants delivered on fetal or maternal indication due to IUGR and PE were found in the ELGAN study [24].…”
Section: Discussionmentioning
confidence: 89%
“…Maternal vitamin D deficiency has been linked to pregnancy complications, including preeclampsia [18,19], preterm birth [20], and intrauterine growth restriction [21], which may promote adverse neonatal outcomes, such as increased future risk of hypertension [22], enteritis [23], asthma [24], and impaired neurodevelopment [25]. Meanwhile, intrauterine/placental inflammation also has been linked to the abovementioned pregnancy-related complications [26] and adverse neonatal outcomes [27], suggesting the possibility of an association between maternal vitamin D deficiency and intrauterine/placental inflammation. Previous reports on the association between vitamin D deficiency and placental function were mostly based on animal studies and showed that vitamin D could inhibit placental inflammation by activating the vitamin D receptor (VDR)/nuclear factor kappa B pathway [28e30], but the evidence is lacking in humans [31,32].…”
Section: Introductionmentioning
confidence: 99%